Discovery of Superior Cu‐GaOx‐HoOy Catalysts for the Reduction of Carbon Dioxide to Methanol at Atmospheric Pressure. Issue 8 (16th March 2016) - Zohour, Bahman; Yilgor, Iskender; Gulgun, Mehmet A.; Birer, Ozgur; Unal, Ugur; Leidholm, Craig; Senkan, Selim
Abstract: Catalytic conversion of carbon dioxide to liquid fuels and basic chemicals by using solar‐derived hydrogen at, or near, ambient pressure is a highly desirable goal in heterogeneous catalysis. If realized, this technology could lead to a more sustainable society together with decentralized power generation. A novel class of holmium‐containing multi‐metal oxide Cu catalysts, discovered through the application of high‐throughput methods, is reported. In particular, ternary systems of Cu‐GaO x ‐HoO y >Cu‐CeO x ‐HoO y ∼Cu‐LaO x ‐HoO y supported on γ‐Al2 O3 exhibited superior methanol production (10×) with less CO formation than previously reported catalysts at 1 atm pressure. Holmium was shown to be highly dispersed as few‐atom clusters, suggesting that the formation of trimetallic sites could be the key for the promotion of methanol synthesis by Ho. Abstract : Three metals are better than two : A novel class of holmium‐containing multi‐metal oxide Cu catalysts, discovered through the application of high‐throughput methods, is reported for the reduction of carbon dioxide to methanol at atmospheric pressure.